STATE RESPONSIBILITY FOR IMPLEMENTING LARGE-SCALE SOCIAL RESTRICTIONS TO COMMUNITIES AFFECTED BY COVID-19 IN SURABAYA CITY - Hezron Sabar Rotua Tinambunan; Hananto Widodo; Elisabeth Septin Puspoayu; Eliza Tiurmaida; Zefanya Annabella (Fakultas Hukum, Universitas Diponegoro, 2022)
There are significant numbers of the people of Surabaya City affected by the Government Regulation of Large-Scale Social Restrictions (PSBB), because they work in informal aspects, such as online motorcycle taxis and street vendors (PKL). Hence, it is necessary for the state to intervene in order to continue providing comfort for its citizens in the PSBB implementation. The purpose of this research is to show the responsibility of the state during the Covid-19 pandemic so as to provide social justice for the entire community. The empirical juridical research method was used to achieve the research objectives. The results of this study showed that the state’s responsibility for the economic and social life of the community was designed by the founding fathers, carried out by the state under any conditions, be it normal conditions or abnormal conditions. The state was responsible for the economic and social life of the community, given the fact that there was a gap between the rich and the poor in the society. Because there were economically and socially vulnerable groups of people, the role of the state was needed to eliminate oppression by the rich to the poor. The state could use its discretionary authority as a form of implementing state responsibilities to the community in accordance with the laws and regulations.